ANALISIS PENCAPAIAN KOMPETENSI KOGNITIF TINGKATAN APLIKASI (C3) DAN ANALISIS (C4) DALAM PEMBELAJARAN FISIKA PADA SISWA KELAS XI SMA PROGRAM RSBI - Karina Sulistyorini, Ayu; Pujayanto, Puja; Yusliana Ekawati, Elvin (Jurnal Pendidikan Fisika, 2013)
The objectives of this study are: (1) Obtaining the information about the results of the analysis cognitive competence achievement of the application level (C3) and analysis level (C4) in learning Physics at XI grade of second semester in RSBI program of SMA Negeri 3 Surakarta in the 2011/2012 Academic Year, (2) Obtaining the information of the difficulties experienced by students and their contributing factors in achieving cognitive competencies of the application level (C3) and analysis level (C4) in learning Physics at XI grade of second semester in RSBI program of SMA Negeri 3 Surakarta in the 2011/2012 Academic Year. This study used a qualitative descriptive research. This study was conducted at SMA Negeri 3 Surakarta and the subjects were students of class XI IPA 5 and XI IPA 7. The sampling technique used were purposive sampling and snowball sampling. This study used testing, interview, and documentation for collecting the data. Because of the data analysis technique used in this study was Miles and Hubermen model, so that the activity in the data analysis included data reduction, data presentation, and conclusion. Based on the data analysis and discussion, in this study can be concluded that: (1) The results of the analysis of cognitive competence achievement of the application level (C3) and analysis level (C4) in learning Physics at XI grade of second semester in RSBI program of SMA Negeri 3 Surakarta in the 2011/2012 Academic Year, as follows: (a) Level of cognitive competence in application level (C3) has reached 70,92% or in satisfactory category; (b) Level of cognitive competence in application level (C4) has reached 69,45%, or inÂ  poor category. (2) The students difficulties in achieving cognitive competence of application level (C3) and analysis level (C4) in Physics and its causes learning difficulties, was shown from the mistakes made by students in answering questions, as follows: (a) At the cognitive level of application (C3) caused by two factors, namely: (i) Students have not been able to identify the relevant information, shown from the interpretation error made ââby the students in doing the test; (ii) Students have not mastered the rules to get a solution, shown from the misconception and the strategic error made by the students in doing the test. (b) At the cognitive level of analysis (C4) caused by two factors, namely: (i) Students have not been able to separate the idea into parts or elements, shown from the strategic error made ââby students in doing the test; (ii) Students have not understood the relationship of all parts thoroughly, shown from the misconception, and the sign error made ââby the students in doing the test. The implication of this research is that teachers can find or develop innovations in teaching Physics that students cognitive competence can be improved. In addition, teachers can find a solution to overcome the difficulties of students in learning, such as by conducting remedial teaching. Keywords: cognitive competence, applicationâs level (C3), analysisâs level (C4), SMA RSBI